PENGARUH LITERASI KEUANGAN, MODAL MINIMAL INVESTASI DAN RISK TERHADAP MINAT MAHASISWA BERINVESTASI DI PASAR MODAL - Agung Santoso; Siti Maghfiroh; Taufik Hidayat (Jurnal Riset Akuntansi Soedirman (JRAS), 2023)
This study aims to determine the effect of financial literacy, minimum investment capital, and risk on student interest in investing in the capital market. This study uses primary data from students at the Faculty of Economics and Business, Jenderal Sudirman University. Data was collected using purposive sampling and was carried out by distributing online questionnaires to respondents who were students at the Faculty of Economics and Business, Jenderal Sudirman University, resulting in a research sample consisting of 100 students. In this study, the data analysis technique used is multiple linear regression analysis. The results of the study state that: (1) financial literacy has a positive effect on student interest in investing in the capital market; (2) minimal capital has a negative effect on student interest in investing in the capital market; (3) risk has a negative effect on student interest in investing in the capital market. The implication of this study is that there are practical implications to explain empirically behavior attitude, subjective norms, and perceived behavior control that affect student interest in investing and can be used as a reference for further research using The Theory of Planned Behavior in discussing investment interests made by students. The theoretical implication is that the Government can also play an active role in improving financial literacy by collaborating with universities to provide education related to financial products or building investment galleries at universities that do not yet have so that public interest, especially students, in investing increases.